Non-Answered Questions in Patients with Endobronchial Valve Placement for Lung Volume Reduction - Caviedes, Iván; Herth, Felix (Respiration, 2018)
Endoscopic lung volume reduction is a minimally invasive procedure performed to reduce the space occupied by the emphysemas’ lobes. This procedure has been demonstrated to be beneficial for patients with advanced chronic obstructive pulmonary disease and severe hyperinflation. The use of endobronchial valves is increasing, as well as the number of reports of adverse events. The most common complications after the procedure are a pneumothorax, bleeding, infections, the need for valve removal, and valve expulsion. We have recently treated a patient who achieved immediate left upper lobe atelectasis but developed a pneumothorax on the 6th day and near-fatal kinking of the left lower lobe bronchus. This patient had asphyctic episodes probably due to a functional left pneumonectomy. We should consider this unusual complication in patients undergoing endoscopic lung volume reduction whose condition worsens after achieving complete lobar atelectasis.
Gesehen am 02.04.2019